Reforms in the Competency Development Strategy of Indigenous Papuan Soldiers in Kodam XVII/Cenderawasih - Anis Misiyanti; M. Azis Muslim (Jurnal Indonesia Sosial Teknologi, 2024)
Affirmation has consequences for the emergence of competency gaps, as happened in the recruitment results of Indigenous Papuan soldiers (OAP) in Kodam XVII/Cenderawasih. So, to overcome this gap, reforms are needed in human resource development, especially in competency development. This paper seeks to examine the competency gaps in OAP soldiers recruited from the affirmation program. The research was conducted using qualitative methods on data obtained through in-depth interviews with several resource persons, namely Kodam XVII/Cenderawasih officials. The results found that the competency gap between OAP soldiers and the competencies needed in military positions requires integrative competency development efforts. This study concludes that the reform of competency development of OAP Soldiers in Kodam XVII / Cenderawasih is essential to overcome the competency gap and prepare them to face the dynamics of the personnel system, especially with the ASN Bill, which demands adequate competence.